Technological transfer in production of Majiayao-style pottery between Neolithic communities in northwest China - Dammer, E (2021)
This study investigates the transfer of technological knowledge in production of the Neolithic Majiayao-style pottery (5300-4000 cal yr BP) on the territories of the modern Chinese provinces Gansu and Qinghai. The Majiayao-style pottery includes fine painted ware and coarse cord-impressed ware. Both wares of the Majiayao style were widely distributed across different river valleys located hundreds of kilometres away from each other. This study investigates whether there are similarities in production technology of the Majiayao-style beyond the shape and decoration and addresses communication and connectivity of prehistoric people living in the Tao River, Huangshui River, and the Yellow River valleys.